The Influence of Compensation and Organizational Climate on Job Satisfaction in The Moderation of Organizational Commitment in Representative Office of Bank Indonesia, North Sumatra Province - Indri Mandasari Pohan; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2024)
This study aims to see the Effect of Compensation and Organizational Climate on Job Satisfaction in Moderation of Organizational Commitment at the Representative Office of Bank Indonesia in North Sumatra Province. Human Resource Management (HRM) is an important factor and the heart of every business. This is due to the alert attitude of the human resource management team towards the workforce of each employee in the company. The results of this study are as follows: Compensation has a negative and insignificant effect on Job Satisfaction and is moderated by organizational commitment with a value of -0.019 and p values 0.455. Organizational Climate has a negative and insignificant effect on Job Satisfaction and is moderated by organizational commitment with a value of -0.074 and p values 0.296. Organizational Climate has a positive and significant effect on Job Satisfaction with a value of 0.273 and p values 0.045. Organizational Commitment has a positive and significant effect on Job Satisfaction with an original sample value of 0.496 and p values 0.000. Compensation has a positive and significant effect on Job Satisfaction with an original sample value of 0.215 and p values of 0.006.